Thinking in c : including object oriented programming with c++ - Mahapatra, P.B (Wheeler Pub., 2001)
Thinking in c : including object oriented programming with c++ / Mahapatra, P.B. -- New Delhi: Wheeler Pub., 2001 005.133C M214 No. of Copies : 1